Error in abstract - Schneider, Ekaterina; Hernández, Cristóbal; Brock, Robert; Eckstein, Monika; Bodenmann, Guy; Heinrichs, Markus; Ehlert, Ulrike; Läuchli, Severin; Ditzen, Beate (JAMA psychiatry, 2025)
In the Original Investigation titled “Intranasal Oxytocin and Physical Intimacy for Dermatological Wound Healing and Neuroendocrine Stress: A Randomized Clinical Trial,” published online November 12, 2025, there was an error in the Results of the Abstract. The value for the association of greater sexual activity with reduced daily cortisol levels should have been b = −0.083. This article has been corrected online.
Gesehen am 14.01.2026